THE INFLUENCE OF INDIVIDUAL CHARACTERISTICS AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT PT. BOSOWA BERLIAN MOTOR, KENDARI BRANCH - Zainuddin, Zainuddin; Djauhar, Asri; HM, Suyuti (Fakultas Ekonomi Dan Bisnis Universitas Sulawesi Tenggara, 2021)
This study aims to determine the effect of individual characteristics and work environment on employee performance at PT. Bosowa Berlian Motor, Kendari Branch. The sample in this study were as many as 43 respondents who were taken census at PT. Bosowa Berlian Motor, Kendari Branch. This study uses multiple linear regression analysis tools. The study results found that simultaneously individual characteristics and work environment have a positive and significant effect on employee performance. Partially individual characteristics and work environment have a positive and significant effect on employee performance.